2016
DOI: 10.4314/bcse.v30i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characterization and DNA binding properties of lanthanide(III) complexes with 2-acetylpyridine isonicotinoylhydrazone (APINH)

Abstract: ABSTRACT. The lanthanide(III) complexes of general formula of [Ln(APINH)2(NO3](NO3)2.nH2O (where, Ln = La, Ce, Pr, Nd, Sm; APINH = 2-acetylpyridine isonicotinoyl hydrazone, n = 0, 2 and 5 for La/Ce/Pr, Sm and Nd complexes, respectively) were synthesized under mild reaction conditions with excellent yields. The complexes were characterized based on elemental analysis, molar conductivity, and infrared spectroscopy. Molar conductivity data suggest that the complexes are 1:2 electrolytes. IR spectral data suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Some of these complexes are known to escalate the biological properties of the original ligand thus triggered many researchers to develop new novel complexes between a biologically active ligand and metal ion (usually the transition metal groups) to improve the ligand biological properties. Several analyses which are frequently used to determine the structure of the complex are elemental analysis, Fourier transform infrared (FTIR) spectroscopy, UV-Vis spectroscopy, nuclear magnetic resonance (NMR), and Raman spectroscopy [30][31][32]. Additionally, the conductivity and magnetic susceptibility behavior of the compounds were often observed.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these complexes are known to escalate the biological properties of the original ligand thus triggered many researchers to develop new novel complexes between a biologically active ligand and metal ion (usually the transition metal groups) to improve the ligand biological properties. Several analyses which are frequently used to determine the structure of the complex are elemental analysis, Fourier transform infrared (FTIR) spectroscopy, UV-Vis spectroscopy, nuclear magnetic resonance (NMR), and Raman spectroscopy [30][31][32]. Additionally, the conductivity and magnetic susceptibility behavior of the compounds were often observed.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction of metal complexes with nucleic acids is an exciting area of research due to their potential use as drugs, tools for biochemical and biomedical applications in gene regulation. Considerable efforts are being made in our laboratories to investigate metal-DNA interactions [4][5][6] and to develop drugs. Thus, looking to the importance of DNA binding agents with essential metal complexes for successful development of antimicrobial agents, herein we report the synthesis, characterization, DNA binding properties and anti bacterial activity of Cu(II), Ni(II), Co(II) and Zn(II) complexes of cuminaldehyde benzoylhydrazone (CABH).…”
Section: Introductionmentioning
confidence: 99%
“…IR data suggest that the ligand acts as mono anionic bidentate ligands in all metal complexes. The non-ligand bands in 692-699 and 508-533 cm -1 regions are tentatively assigned to ν (M-O), and ν (M-N) vibrations9 , respectively.…”
mentioning
confidence: 95%
“…It can react with aldehydes to form isonicotinohydrazones, which show interesting biological activities [1][2][3][4]. Moreover, isonicotinohydrazone compounds usually possess three or more donor atoms, which can readily form complexes with various metal atoms [5][6][7][8][9][10][11][12]. Recently, we found that halido-substituted hydrazones have potential antimicrobial activities [13].…”
Section: Introductionmentioning
confidence: 99%